Subthreshold modeling of ambipolar organic field-effect transistor based on field-dependent mobility. (2022) - Katiyar, Suleshma; Jogi, Jyotika
Abstract: In the present work, an ambipolar charge transport model based on the field dependent mobility is presented for the electron accumulation mode. The model is derived using the charge drift approach, which is later extended to include subthreshold ambipolar region, using an asymptotically interpolation function. A methodology for the extraction of model parameters is discussed. The extracted parameters are then used to obtain the field dependent mobility for both holes and electrons. The role of traps in modulating the electron and hole mobility as a function of gate voltage is presented. It is demonstrated that the output and transfer characteristics obtained from the model are in close proximity with the experimental results presented by of Zhang et al. (2017).